Quality of communication between dentists and dental laboratory technicians for fixed prosthodontics in Riyadh, Saudi Arabia - Huda Tulbah; Eman AlHamdan; Amal AlQahtani; Asma AlShahrani; Mona AlShaye (Elsevier, 2017)
The fabrication of a clinically acceptable dental prosthesis requires proper communication between the dentist and the dental technician. Prosthodontic educators have been concerned with this interaction and communication. Fixed prosthodontics laboratories revealed that the technicians are often dissatisfied with the information provided in work authorizations. Objective: To evaluate the quality of communication between dentists and laboratory technicians via work authorizations for fixed prosthodontics in both governmental and private dental laboratories in Riyadh area from the technician's perspective. Methods: A sample of 66 dental laboratories, including all government dental laboratories and a selected number of randomly chosen private dental laboratories from each district of Riyadh (40%), participated in the survey.A questionnaire was developed to include questions related to the following areas of work authorization: clarity and accuracy of instructions, patient information, type of prosthesis, choice of materials, design and shade of the prosthesis and type of porcelain glaze. The questionnaire was answered in a face-to-face interview by technicians who were qualified in fixed prosthetic work. Data were analyzed through parametric tests (T-test and one-way ANOVA) to identify significant values (P < 0.05). Results: This survey showed a lack of communication between dentists and dental laboratories regarding the following: marginal design, pontic design, staining diagram, type of porcelain and glaze needed for the prosthesis. Significant differences were observed between the government and private dental laboratories. There was a greater lack of communication between the dentists and government laboratory technicians in Riyadh.There was no statistically significant difference between private laboratories of different areas in Riyadh city (P < 0.05). Conclusion: The quality of communication between dentists and dental technicians in Riyadh can sometimes be inadequate, and governmental laboratories have a lower level of communication. Keywords: Dentist, Dental technician, Fixed prosthodontics, Communication, Work authorization form